Enhancing the antibacterial activity of light-activated surfaces containing crystal violet and ZnO nanoparticles: investigation of nanoparticle size, capping ligand, and dopants - Sehmi,SK; Noimark,S; Pike,SD; Bear,JC; Peveler,WJ; Williams,CK; Shaffer,MSP; Allan,E; Parkin,IP; MacRobert,AJ (ACS OMEGA, 2016)
Healthcare-associated infections pose a serious risk for patients, staff, and visitors and are a severe burden on the National Health Service, costing at least £1 billion annually. Antimicrobial surfaces significantly contribute toward reducing the incidence of infections as they prevent bacterial adhesion and cause bacterial cell death. Using a simple, easily upscalable swell–encapsulation–shrink method, novel antimicrobial surfaces have been developed by incorporating metal oxide nanoparticles (NPs) and crystal violet (CV) dye into medical-grade polyurethane sheets. This study compares the bactericidal effects of polyurethane incorporating ZnO, Mg-doped ZnO, and MgO. All metal oxide NPs are well defined, with average diameters ranging from 2 to 18 nm. These materials demonstrate potent bactericidal activity when tested against clinically relevant bacteria such as Escherichia coli and Staphylococcus aureus. Additionally, these composites are tested against an epidemic strain of methicillin-resistant Staphylococcus aureus (MRSA) that is rife in hospitals throughout the UK. Furthermore, we have tested these materials using a low light intensity (∼500 lx), similar to that present in many clinical environments. The highest activity is achieved from polymer composites incorporating CV and ∼3 nm ZnO NPs, and the different performances of the metal oxides have been discussed.